Co-transduction of dual-adeno-associated virus vectors in the neonatal and adult mouse utricles - Chen, Zhong-Rui; Guo, Jing-Ying; He, Lu; Liu, Shan; Xu, Jun-Yi; Yang, Zi-Jing; Su, Wei; Liu, Ke; Gong, Shu-Sheng; Wang, Guo-Peng (Frontiers in Molecular Neuroscience, 2022)
Adeno-associated virus (AAV)-mediated gene transfer is an efficient method of gene over-expression in the vestibular end organs. However, AAV has limited usefulness for delivering a large gene, or multiple genes, due to its small packaging capacity (< 5 kb). Co-transduction of dual-AAV vectors can be used to increase the packaging capacity for gene delivery to various organs and tissues. However, its usefulness has not been well validated in the vestibular sensory epithelium. In the present study, we characterized the co-transduction of dual-AAV vectors in mouse utricles following inoculation of two AAV-serotype inner ear (AAV-ie) vectors via canalostomy. Firstly, co-transduction efficiency was compared between dual-AAV-ie vectors using two different promoters: cytomegalovirus (CMV) and CMV early enhancer/chicken β actin (CAG). In the group of dual AAV-ie-CAG vectors, the co-transduction rates for striolar hair cells (HCs), extrastriolar HCs, striolar supporting cells (SCs), and extrastriolar SCs were 23.14 ± 2.25%, 27.05 ± 2.10%, 57.65 ± 7.21%, and 60.33 ± 5.69%, respectively. The co-transduction rates in the group of dual AAV-ie-CMV vectors were comparable to those in the dual AAV-ie-CAG group. Next, we examined the co-transduction of dual-AAV-ie-CAG vectors in the utricles of neonatal mice and damaged adult mice. In the neonatal mice, co-transduction rates were 52.88 ± 3.11% and 44.93 ± 2.06% in the striolar and extrastriolar HCs, respectively, which were significantly higher than those in adult mice. In the Pou4f3+/DTR mice, following diphtheria toxin administration, which eliminated most HCs and spared the SCs, the co-transduction rate of SCs was not significantly different to that of normal utricles. Transgene expression persisted for up to 3 months in the adult mice. Furthermore, sequential administration of two AAV-ie-CAG vectors at an interval of 1 week resulted in a higher co-transduction rate in HCs than concurrent delivery. The auditory brainstem responses and swim tests did not reveal any disruption of auditory or vestibular function after co-transduction with dual-AAV-ie vectors. In conclusion, dual-AAV-ie vectors allow efficient co-transduction in the vestibular sensory epithelium and facilitate the delivery of large or multiple genes for vestibular gene therapy.